Changes in Movements of Chinook Salmon between Lakes Huron and Michigan after Alewife Population Collapse. (1st November 2017) - Clark, Richard D.; Bence, James R.; Claramunt, Randall M.; Clevenger, John A.; Kornis, Matthew S.; Bronte, Charles R.; Madenjian, Charles P.; Roseman, Edward F.
Abstract: Alewives Alosa pseudoharengus are the preferred food of Chinook Salmon Oncorhynchus tshawytscha in the Laurentian Great Lakes. Alewife populations collapsed in Lake Huron in 2003 but remained comparatively abundant in Lake Michigan. We analyzed capture locations of coded‐wire‐tagged Chinook Salmon before, during, and after Alewife collapse (1993–2014). We contrasted the pattern of tag recoveries for Chinook Salmon released at the Swan River in northern Lake Huron and Medusa Creek in northern Lake Michigan. We examined patterns during April–July, when Chinook Salmon were primarily occupied by feeding, and August–October, when the salmon were primarily occupied by spawning. We found evidence that Swan River fish shifted their feeding location from Lake Huron to Lake Michigan after the collapse. Over years, proportions of Swan River Chinook Salmon captured in Lake Michigan increased in correspondence with the Alewife decline in Lake Huron. Mean proportions of Swan River fish captured in Lake Michigan were 0.13 (SD = 0.14) before collapse (1993–1997) and 0.82 (SD = 0.22) after collapse (2008–2014) and were significantly different. In contrast, proportions of Medusa Creek fish captured in Lake Michigan did not change; means were 0.98 (SD = 0.05) before collapse and 0.99 (SD = 0.01) after collapse. The mean distance to the center of the coastal distribution of Swan River fish during April–July shifted 357 km (SD = 169) from central Lake Huron before collapse to central Lake Michigan after collapse. The coastal distributions during August–October were centered on the respective sites of origin, suggesting that Chinook Salmon returned to release sites to spawn regardless of their feeding locations. Regarding the impact on Alewife populations, this shift in interlake movement would be equivalent to increasing the Chinook Salmon stocking rate within Lake Michigan by 30%. The primary management implication is that interlake coordination of Chinook Salmon stocking policies would be expected to benefit the recreational fishery. Received August 26, 2017; accepted September 4, 2017 Published online November 1, 2017